2010
DOI: 10.1177/0192623310364028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Cigarette Smoke Exposure on Fischer 344 Rats and on Selected Lung Proteins

Abstract: A short-term 5-day cigarette smoke exposure study was conducted in Fischer 344 rats to identify smoke-induced lung protein changes. Groups of 10 male and 10 female rats at 5 weeks of age were randomly assigned to one of four exposure groups. Animals received filtered air (control) or 75, 200, or 400 mg total particulate matter (TPM)/m 3 of diluted Kentucky reference 3R4F cigarette smoke. Nose-only exposures were conducted for 3 hours/day for 5 consecutive days. Mean body weights were significantly reduced only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…5 at an average of 108.7 ± 72.8 mg/m 3 during the study period. Consistently, in previous reports, mice were exposed to CS at an average of 90-100 mg/m 3 (Chen et al, 2005;Carter and Misra, 2010;Schweitzer et al, 2011;Siggins et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5 at an average of 108.7 ± 72.8 mg/m 3 during the study period. Consistently, in previous reports, mice were exposed to CS at an average of 90-100 mg/m 3 (Chen et al, 2005;Carter and Misra, 2010;Schweitzer et al, 2011;Siggins et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Compared with bone marrow-and gingival tissue-derived MSCs, hUC-MSCs have been determined to display the highest immunomodulatory ability (Li et al, 2018). Doses of hUC-MSC between 1 × 10 6 and 4 × 10 6 cells/ml have been deemed effective in a previous study (Chen et al, 2005;Carter and Misra, 2010;Lin et al, 2017). For example, the hUC-MSC concentration of 3 × 10 6 cells/ml was administered in lung disease (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, K8 and K18 may have been upregulated in order to moderate JNK signaling and to suppress inflammation and apoptosis. In contrast, another study in rats that had been exposed to tobacco smoke for 5 days reported that the intensity of staining for JNK in epithelial cells in lung parenchyma and for protein kinase C‐α (PKC‐α) in macrophages were increased, suggesting that PKC‐α is activated by exposure to tobacco smoke and leads to the activation of NF‐κB through the activation of JNK [53]. In addition, another study has reported increased expression of JNK and ERK2 following prolonged (over 1 month) exposure to tobacco smoke [54].…”
Section: Discussionmentioning
confidence: 92%
“…During the development of COPD, cigarette smoke extract was reported to affect the protective activity of MRP1 on lung tissue [ 24 ]. Additional studies reported that JNK expression in lung parenchyma was increased after tobacco smoke exposure for 5 days in rats and 4–12 weeks in guinea pigs [ 36 , 37 ]. In contrast, upregulation of phosphorylated keratin type 2 cytoskeletal 8 (K8) and keratin type 1 cytoskeletal 18 (K18) is to moderate JNK signaling in lung tissue of rats after a short time of tobacco smoke exposure [ 38 ].…”
Section: Discussionmentioning
confidence: 99%